1999
DOI: 10.1016/s0014-5793(99)00266-5
|View full text |Cite
|
Sign up to set email alerts
|

Human members of the SCO1 gene family: complementation analysis in yeast and intracellular localization

Abstract: Cytochrome c oxidase is a multiprotein complex in the mitochondrial membrane whose biogenesis requires a number of proteins besides the structural subunits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 24 publications
0
30
0
2
Order By: Relevance
“…In the human genome two genes have been identified, hSCO1 located on chromosome 17p12-13 and hSCO2 on chromosome 22q13. Both encode mt proteins (Petruzzella et al, 1998;Paret et al, 1999), which are essential for mt function as shown by the recent detection of mutations associated with fatal COX deficiencies. Mutations in hSCO2 were reported in infants who suffered from a fatal disorder with hypertrophic cardiomyopathy as the predominant symptom (Papadopoulou et al, 1999;Jaksch et al, 2000Jaksch et al, , 2001a whereas the key symptoms of the infant patients carrying mutations in the hSCO1 gene were hepatic failure and ketoacidotic coma (Valnot et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the human genome two genes have been identified, hSCO1 located on chromosome 17p12-13 and hSCO2 on chromosome 22q13. Both encode mt proteins (Petruzzella et al, 1998;Paret et al, 1999), which are essential for mt function as shown by the recent detection of mutations associated with fatal COX deficiencies. Mutations in hSCO2 were reported in infants who suffered from a fatal disorder with hypertrophic cardiomyopathy as the predominant symptom (Papadopoulou et al, 1999;Jaksch et al, 2000Jaksch et al, , 2001a whereas the key symptoms of the infant patients carrying mutations in the hSCO1 gene were hepatic failure and ketoacidotic coma (Valnot et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Like SURF1, SCO1 and SCO2 are mitochondrial inner membrane proteins (21)(22)(23). SCO proteins have a conserved CXXXC motif protruding into the intermembrane space, similar to the CXXXC motif present at the Cu A site of MTCO2 (24).…”
mentioning
confidence: 99%
“…Human Sco1 and Sco2 are nonfunctional in yeast sco1⌬ cells (15). However, a chimeric protein consisting of 158 residues from the N terminus of yeast Sco1 fused to a C-terminal segment of hSco1, but not hSco2, is functional.…”
mentioning
confidence: 99%
“…However, a chimeric protein consisting of 158 residues from the N terminus of yeast Sco1 fused to a C-terminal segment of hSco1, but not hSco2, is functional. A P174L substitution was found to attenuate its function (15,16), although the CcO deficiency in yeast sco1⌬ cells harboring the mutant yeast/human Sco1 chimera could be rescued for growth on a nonfermentable carbon by the addition of 0.2% CuSO 4 (16). This suggests that P174L Sco1 retains some residual function; however, the molecular defect in Sco1 function that results from this amino acid substitution remains unknown.…”
mentioning
confidence: 99%